Applications of CRISPR screening to lung cancer treatment - Shen, Wanying; Hu, Fangli; Lei, Pan; Tang, Yijun (Frontiers in Cell and Developmental Biology, 2023)
Lung cancer is an extremely aggressive and highly prevalent disease worldwide, and it is one of the leading causes of cancer death. Deciphering intrinsic genetic mechanism, finding new targets, and overcoming drug resistance are the key to lung cancer treatment. High-throughput CRISPR screening has been extensively used to obtain the genes related to cancers including lung cancer. This review describes CRISPR/Cas9 or CRISPR/dCas9-based technologies for high-throughput screening. We summarize the applications of CRISPR screening technology in exploring the mechanism of lung cancer development in vivo or in vitro, overcoming drug resistance, improving the effect of immunotherapy, and discovering new therapeutic targets. This review highlights the potential of CRISPR screening in combination with tumor barcoding and high-throughput sequencing (Tuba-seq) to precisely quantify the impact of alterations in many tumor suppressor genes on lung cancer.